2020
DOI: 10.1126/science.aax3338
|View full text |Cite
|
Sign up to set email alerts
|

Huntington’s disease alters human neurodevelopment

Abstract: Although Huntington’s disease is a late-manifesting neurodegenerative disorder, both mouse studies and neuroimaging studies of presymptomatic mutation carriers suggest that Huntington’s disease might affect neurodevelopment. To determine whether this is actually the case, we examined tissue from human fetuses (13 weeks gestation) that carry the Huntington’s disease mutation. These tissues showed clear abnormalities in the developing cortex, including mislocalization of mutant huntingtin and junctional complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
202
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 238 publications
(225 citation statements)
references
References 40 publications
11
202
0
3
Order By: Relevance
“…In addition, inhibition of ECM1, which is associated with lipoid proteinosis that may result in epilepsy, neuropsychiatric disorders, and spontaneous CNS hemorrhage, resulted in a significant effect [52]. Interestingly, knockdown of HDAC3, which has a similar average expression and variability in HD NPCs, and was previously shown to be related to HD cognitive pathology and CAG repeat expansion but not to aggregate formation in mouse HD models [7], showed a slightly significant increase in cellular aggregates. Finally, although both CCT5 and CCT7 are known to contribute to protein aggregation through autophagy regulation [44], only CCT7, which was shown to interact and affect GPCR aggregation [43], showed an effect in our NPCs.…”
Section: P Hmentioning
confidence: 94%
“…In addition, inhibition of ECM1, which is associated with lipoid proteinosis that may result in epilepsy, neuropsychiatric disorders, and spontaneous CNS hemorrhage, resulted in a significant effect [52]. Interestingly, knockdown of HDAC3, which has a similar average expression and variability in HD NPCs, and was previously shown to be related to HD cognitive pathology and CAG repeat expansion but not to aggregate formation in mouse HD models [7], showed a slightly significant increase in cellular aggregates. Finally, although both CCT5 and CCT7 are known to contribute to protein aggregation through autophagy regulation [44], only CCT7, which was shown to interact and affect GPCR aggregation [43], showed an effect in our NPCs.…”
Section: P Hmentioning
confidence: 94%
“…There is mounting evidence that disorders identified in childhood and adulthood may have their origins and manifestations during early development (Figure 4). These include structural birth defects [111][112][113][114] , neurodevelopmental disorders including Huntington's disease 115 Moreover, many adult cancers recapitulate a grotesque version of human developmental programs 124 . Conversely, molecular processes that guide human development can be understood by studying developmental disorders 125 , many with significant individual and public health impacts.…”
Section: Clinical Relevance and Applications Of A Human Developmentalmentioning
confidence: 99%
“…Huntington’s disease (HD) is caused by a CAG trinucleotide repeat expansion in the huntingtin gene ( HTT ), which encodes an expanded polyglutamine stretch in the huntingtin protein (HTT). Cumulative cellular and molecular studies have demonstrated that brain developmental abnormalities may be a substrate for impaired brain function and later neurodegeneration in HD ( Mehler and Gokhan 2000 ; Reiner et al 2003 ; Cattaneo et al 2005 ; Godin et al 2010 ; Molina-Calavita et al 2014 ; Conforti et al 2018 ; Wiatr et al 2018 ; Barnat et al 2020 ). The HD brain pathology may therefore represent, at least partially, the consequences of abnormal development.…”
Section: Introductionmentioning
confidence: 99%